Figurative Language in Four Song Lyrics From The Smashing Pumpkins’ Mellon Colie and Infinite Sadness Album - Krishna Arya Putra, Putu (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p25, 2018)
The topic discussed in this paper is Figurative Language in four song lyrics from The Smashing Pumpkins’ Mellon Collie and Infinite Sadness viewed from context of situation. Figurative languages may bring difficulties in understanding the kind of figurative languages contained in the song lyrics, but this study tried to find the actual meanings and the various kind of the figurative languages from the data source and that was the reason for choosing the topic “Figurative Language in Four Song Lyrics from The Smashing Pumpkins’ Mellon Collie and The Infinite Sadness”. The analysis is focused on two main problems: what types of figurative languages are found in four song lyrics from The Smashing Pumpkins’ Mellon Collie and Infinite Sadness album and what are the meaning of figurative languages found in four song lyrics from The Smashing Pumpkin’ Mellon Collie and Infinite Sadness album. The main theory proposed by Knickerbocker and Reninger (1963) and supported by the theory from Leech (1974) were related to this research and useful to get the other information about the data. The conclusion of this paper showed that there were six kind of figurative languages found, there were: metaphor, hyperbole, simile, paradox, synecdoche and personification. Mostly from the four song lyrics above, Corgan used figurative language of metaphor and simile as his writing style to deliver his message to the listener. There were three kind of the theory of meaning found in this four song lyrics, there are: collocative meaning, connotative meaning and affective meaning.